Economic Valuation of Mangrove Forest Ecosystem in Sinjai - Tahang, Hamzah; Amiluddin, Amiluddin; Amir, Faisal; Firman, Firman (Torani Journal of Fisheries and Marine Science, 2018)
This study aims to identify the type and function of ecosystems of mangrove forests, in Sinjai district and calculate the total economic value of mangrove ecosystems. The analytical method used is economic valuation and willingness to pay community. The results showed that species dominating Rhyzopora sp, Avicennia sp Sonneratia sp and Bruguera sp. The direct benefits to the community from mangrove forest in the area of research are firewood, nipa roof, fish and crabs and bats with economic value of Rp 8,598,020,500 with average value per ha 11,343,117. Indirect value consists of wave breaks of Rp 4,480,000,000 or Rp 448,000,000 / year with an estimated life of the building for 10 years and a carbon sequestration benefit of Rp 153,495,000 a year. Benefit value of Rp203, 250 per ha. The result is multiplied by the total area of the existing mangrove forest ecosystem of 758 Ha, with a total value of biodiversity benefits of Rp 154,063,500 per year. The value of the existence benefit of RP 446,260 ha / yr. With a total area of 758 mangroves, the total benefit of the existence of mangrove ecosystems in Kabupatem Sinjai amounted to Rp 338,265,080 / year. The economic benefit value of Total mangrove sinjai is Rp 13,723,844,080 while the total benefit value per ha is Rp 22,816,656 per year.Keywords: Bennefit economic, Mangrove ecosystem, economic valuaition, Sinjai